Marhaenism Ideology as a Contextual Interpretation Practice of the Values of Independence and Social Justice in the Qur'an - Yasin, Nur Ali; Masnida, Masnida (Unisia, 2025)
This article discusses the relationship between the ideology of Marhaenism initiated by Soekarno and the values ​​of independence and social justice in the Qur'an. Marhaenism was born from concern for the conditions of the common people who do not have the means of production and are often victims of an unfair system. On the other hand, the Qur'an contains teachings about the importance of working hard, living independently, and upholding social justice. Through a qualitative approach with a literature study method, this article examines the texts of the Qur'an accompanied by interpretations from the Ulama', and the works of Soekarno's thought to find common ground between the two. The results of the study show that Marhaenism can be seen as a contextual interpretation of Qur'anic values, especially in fighting for a just, independent society, and free from oppression. Thus, the integration of Islamic teachings and Marhaenism can be an ethical foundation in building social justice in Indonesia.